2018
DOI: 10.1038/s41541-018-0066-4
|View full text |Cite
|
Sign up to set email alerts
|

Induction of neutralizing antibody response against koala retrovirus (KoRV) and reduction in viral load in koalas following vaccination with recombinant KoRV envelope protein

Abstract: Koala retrovirus (KoRV) infects the majority of Australia’s koalas (Phascolarctos cinereus) and has been linked to several life-threatening diseases such as lymphoma and leukemia, as well as Chlamydia and thus poses a threat to the continued survival of this species. While quarantine and antiretroviral drug treatment are possible control measures, they are impractical, leaving vaccination as the only realistic option. In this study, we examined the effect of a recombinant envelope protein-based anti-KoRV vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(63 citation statements)
references
References 42 publications
1
61
1
Order By: Relevance
“…Immune responses to the virus have been shown to vary between these populations in other studies 33,34 . QLD animals may become immunologically tolerant to the virus through in-utero expression of endogenous viral genes, resulting in an inability to respond effectively to infection by exogenous virus in later life, leading to high viral loads.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Immune responses to the virus have been shown to vary between these populations in other studies 33,34 . QLD animals may become immunologically tolerant to the virus through in-utero expression of endogenous viral genes, resulting in an inability to respond effectively to infection by exogenous virus in later life, leading to high viral loads.…”
Section: Discussionmentioning
confidence: 90%
“…showing no detectable antibodies 35 while others reported that Qld koalas in fact produced antibodies to multiple KoRV antigens 34 . In contrast, it has been suggested that SA animals might be infected only with an exogenous virus and as such are able to mount an immune response to the virus, as shown in a study in which both KoRV positive and negative koalas developed KoRV antibodies upon vaccination 34 . Conversely, it is also possible that SA koalas might possess partial replication-defective endogenous KoRV sequences, which provide protection against exogenous virus replication.…”
Section: Discussionmentioning
confidence: 97%
“…Total anti-KoRV IgG antibody levels were determined from serum as detailed in reference 37. Briefly, a near full-length recombinant KoRV-A env protein, minus the first 100 amino acids (inclusion of the first 100 amino acids prevented protein expression, therefore the recombinant protein begins at the RBD), was generated with a glutathione S-transferase (GST) tag for affinity purification (37). To compare the env protein conservation between KoRV subtypes, full-length env protein sequences were compared from KoRV-A (AF151794, BAN63359.1), KoRV-B (NC_021704.1, BAN63358.1), KoRV-C (ALX81658.1, BAN63361.1), KoRV-D (BAN63360.1), and KoRV-F (ANT96689.1).…”
Section: Methodsmentioning
confidence: 99%
“…Assay plates were coated with 1 g recombinant KoRV-A env protein overnight before washing and incubating with serially diluted serum samples. After additional washing, incubation with a sheep anti-koala IgG, further washing, incubation with a donkey anti-sheep horseradish peroxidase (HRP) IgG, final washing, and development with tetramethylbenzidine (TMB) liquid substrate (Sigma-Aldrich), optical density was read at 450 nm and endpoint titers (EPT) calculated (37).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of high levels of the various KoRV-subtypes in multiple tissues, including blood, and the endogenous source of KoRV that cannot be eliminated through breeding, all provide multiple exposure opportunities. While the stability of infectious KoRV in the environment is currently unknown, other gammaretroviruses like feline leukemia virus can survive for at least two days in culture medium but are inactivated after only a few hours if dried (43). Biosafety practices and procedures for persons handling koalas are important to prevent zoonotic exposures.…”
Section: Discussionmentioning
confidence: 99%